2013
DOI: 10.7897/2230-8407.04930
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Bonding Efficacy of Sixth, Seventh and Eighth Generation Bonding Agents: An in Vitro Study

Abstract: The aim of the study was to compare In-vitro the micro tensile bond strength of sixth generation (Clearfil SE Bond, Kuraray, Japan), seventh generation (Adper Easy One, 3 M ESPE, Germany) and eighth generation ((Futurabond DC, Voco, Germany) dentin bonding agents. Twenty freshly extracted caries free, unrestored human molars were selected. The occlusal surfaces were ground flat; divided into four groups of five each according to the bonding agent applied and covered with composite resin (10 mm in height). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The 8th-generation bonding group has nano-sized cross-linking agents that increase its bonding potential to hydroxyapatite. It also has silica particles, as well as the benefits of being dual-cure (17). On the other hand, the presence of BTH (butylated hydroxyl toluene) in G-Premio can be a factor for its high bandwidth.…”
Section: Discussionmentioning
confidence: 99%
“…The 8th-generation bonding group has nano-sized cross-linking agents that increase its bonding potential to hydroxyapatite. It also has silica particles, as well as the benefits of being dual-cure (17). On the other hand, the presence of BTH (butylated hydroxyl toluene) in G-Premio can be a factor for its high bandwidth.…”
Section: Discussionmentioning
confidence: 99%
“…Other variables like functional monomers, cross-linking monomers, solvents, inhibitors and activators can have various bonding that can influence the bond strength. Furthermore, the substrate (composite, dentin, enamel, etc), type of the performed test for bond strength, storage duration and aging conditions of the substrate affect the results, as well (31).…”
Section: Discussionmentioning
confidence: 99%
“…10-MDP in universal bonding makes chemical bond with with hydroxyapatite crystals. Moreover, similar functional chemical monomers bond oxides by hydrophilic phosphate terminals and copolymerized with resin monomers through the hydrophobic methacrylate terminal (31,36).…”
mentioning
confidence: 99%
“…19 Previous studies by Joseph in 2013 and Kable et al in 2015 reported that generation VIII showed the highest tensile strength. The study compared the VI, VII, and VIII bonding materials on the teeth without bleaching application, 20,21 whereas this study compared the V and VIII generation post extracoronal bleaching.…”
Section: Discussionmentioning
confidence: 99%